2021
DOI: 10.1161/jaha.120.018696
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variations in Heart Failure Quality and Outcomes: Get With The Guidelines–Heart Failure Registry

Abstract: Background Regional patient characteristics, care quality, and outcomes may differ based on a variety of factors among patients hospitalized for heart failure (HF). Regional disparities in outcomes of cardiovascular disease have been suggested across various regions in the United States. This study examined whether there are significant differences by region in quality of care and short‐term outcomes of hospitalized patients with HF across the United States. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 23 publications
4
49
6
1
Order By: Relevance
“…23,27,28 The mean age (72.2 years) of patients in the GWTG-HF registry from the USA was higher by almost a decade than that observed in our study. 28 Comparable age was observed in all three local single-centre studies, including IJN ADHF registry, SGH-HF and UiTM Sungai Buloh (mean age of 62, 59 and 63, respectively). 24,25 These findings suggest that HF patients in Malaysia are relatively younger, which is not surprising.…”
Section: Hospitalized Hf Patient Profile In Malaysiacontrasting
confidence: 57%
See 1 more Smart Citation
“…23,27,28 The mean age (72.2 years) of patients in the GWTG-HF registry from the USA was higher by almost a decade than that observed in our study. 28 Comparable age was observed in all three local single-centre studies, including IJN ADHF registry, SGH-HF and UiTM Sungai Buloh (mean age of 62, 59 and 63, respectively). 24,25 These findings suggest that HF patients in Malaysia are relatively younger, which is not surprising.…”
Section: Hospitalized Hf Patient Profile In Malaysiacontrasting
confidence: 57%
“…23,27 However, a much higher proportion of females (48.2%) was observed in the GWTG-HF registry from the USA than was seen in our analysis. 28 Of the hospitalized HF patients in this study, 62.9% had reduced ejection fraction. A relatively lower proportion of HFrEF patients was reported in the SGH-HF (51%), UiTM Sungai Buloh (40.8%) and ADHERE-AP (53%) populations, indicating that half of the hospitalized HF patients had HFmrEF and HFpEF.…”
Section: Hospitalized Hf Patient Profile In Malaysiamentioning
confidence: 77%
“…29 Geographic regionality may influence differences in health care utilization and practice patterns. [30][31][32] The potential for variations in the delivery of care has led to new clinical practice guidelines that describe ways that providers can increase value in the US health care system. 11,29 Renewed health policy models now evaluate health systems' payment structures to determine the effectiveness of therapies of HF outcomes and costs.…”
Section: Discussionmentioning
confidence: 99%
“…QI sets are commonly developed through the following process: literature review, identification of domains, and selection of the final QI set through a consensus process such as the Delphi method [ 8 ]. Some studies have shown that an evidence-practice gap exists in real-world practice, such as early reperfusion in patients with ACS [ 9 , 10 ]. Furthermore, high attainment of the QI set has been associated with lower risk-adjusted mortality [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that an evidence-practice gap exists in real-world practice, such as early reperfusion in patients with ACS [ 9 , 10 ]. Furthermore, high attainment of the QI set has been associated with lower risk-adjusted mortality [ 9 , 10 ]. Although many QI sets are related to acute cardiovascular diseases [ 11 , 12 ], a comprehensive summary is lacking.…”
Section: Introductionmentioning
confidence: 99%